Pengaruh Servant Leadership Terhadap Organizational Citizenship Behavior Dengan Kepuasan Kerja Sebagai Variabel Mediasi: Studi Pada CV. Bali Harmoni Bali Zoo - I Gede Nala Nandana; Made Surya Putra (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
Organizational Citizenship has a positive impact on organizational effectiveness. One factor that can effect OCB is servant leadership, namely a leadership style that focuses on serving team members. Job satisfaction acts as a intervening variable in this research, where job satisfaction is a variable that bridges the effect of servant leadership on OCB. This research aims to analyze and explain the effect of servant leadership on OCB with job satisfaction as a mediating variable. By using a quantitative approach, this research is expected to provide insight into how servant leadership can encourage OCB behavior by increasing employee job satisfaction. This research was conducted on employees of the CV operational division. Bali Harmoni Bali Zoo, with a total sample of 75 employees obtained using the saturated sampling method. Data collection was carried out by interviews and distributing questionnaires. The analysis technique used is Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach. The results of the analysis show that 1) servant leadership has a positive and significant effect on employee OCB, 2) servant leadership has a positive and significant effect on employee job satisfaction, 3) job satisfaction has a positive and significant effect on employee OCB, 4) job satisfaction mediates the effect of servant leadership on Employee OCB. The implications of this research theoretically support the findings of previous research through the perspective of social exchange theory. The practical Behavior is extra-role behavior carried out voluntarily by employees and implications of this research provide a policy reference for organizational leaders and management to increase employee OCB through servant leadership and job satisfaction.